Synchronous presentation of giant anterior neck lipoma and interarytenoid hamartoma - Ali, Roshan; Sattien, Arun Maran; Lucy, Liano; Thingbaijam, Sudhiranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Giant lipomas are benign soft tissue tumor found rarely in the neck and are still rarer in the anterior part of neck. Laryngeal hamartoma (LH) is a very rare lesions and the number of reported cases is limited. Herein, we report a case of 68 years old male with a history of painless, slow growing swelling on anterior neck for past 8 years and also complaints of dyspnoea and stridor for past 6 months. FNAC from anterior neck swelling was suggestive of lipoma. USG and CT findings were suggestive of soft tissue lesions. Indirect and flexible laryngoscopy shows a large pedunculated, globular mass in interarytenoid region. A complete surgical excision of the anterior neck mass and interarytenoid polyp was done. Diagnosis of lipoma and hamartoma was confirmed on histopathology. Patient was followed up for 2 years with no evidence of recurrence.